Property taxes and tax revolts the legacy of proposition 13 - O'Sullivan, Arthur; Sexton, Terri A.; Sheffrin, Steven M. (Cambridge Univ. Pr., 1995)
Property tax revolts have been a much-publicized feature of contemporary political life in the United States and abroad. Focusing on California's experience with Proposition 13, which has had potentially far-reaching political ramifications yet whose effects and possible alternatives have been little understood, this book examines the causes and consequences of property tax revolts